2016
DOI: 10.1161/circimaging.116.004888
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Structure and Function in Hypertensive Disorders of Pregnancy

Abstract: C ardiac disease is the leading non-obstetric cause of death in pregnancy and the puerperium. 1 In uncomplicated pregnancy, there is no significant change in systolic blood pressure.2,3 Diastolic blood pressure and mean arterial pressure decrease during the first trimester and then plateau in the second trimester before rising in the final weeks of pregnancy. 2,3 Hypertension is seen in 6% to 8% of pregnancies 4 and the incidence is increasing as the obstetric population becomes older and more obese. 5 Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 69 publications
1
102
0
Order By: Relevance
“…Several studies assessed the relationship between HDP and the subsequent development of asymptomatic (stage B) or symptomatic (stage C) heart failure (97,101). The American Heart Association and American College of Cardiologists define asymptomatic stage B heart failure as any subject being affected by LV hypertrophy or dysfunction (102).…”
Section: Asymptomatic Heart Failurementioning
confidence: 99%
“…Several studies assessed the relationship between HDP and the subsequent development of asymptomatic (stage B) or symptomatic (stage C) heart failure (97,101). The American Heart Association and American College of Cardiologists define asymptomatic stage B heart failure as any subject being affected by LV hypertrophy or dysfunction (102).…”
Section: Asymptomatic Heart Failurementioning
confidence: 99%
“…A recent systematic review, summarizing 19 echocardiographic studies in pregnancy demonstrated that increased left ventricular mass and total vascular resistance were the most consistent findings in preeclampsia (Castleman et al . ). The finding of diastolic dysfunction and left ventricular remodelling were seen before clinical manifestation of preeclampsia, more marked in severe and early‐onset disease, and also associated with adverse pregnancy outcomes.…”
Section: Cardiovascular and Renal Characteristics Of Preeclampsiamentioning
confidence: 97%
“…A major inconsistency with this hypothesis is that regardless of gestation, preeclampsia is consistently associated with reduced stroke volume and higher/normal total vascular resistance (Castleman et al . ). The latter is in keeping with the findings of hypertension and myocardial dysfunction in both early and late preeclampsia (Melchiorre et al .…”
Section: Cardiovascular and Renal Characteristics Of Preeclampsiamentioning
confidence: 97%
See 1 more Smart Citation
“…Echocardiography and Doppler ultrasound have been widely used for the assessment of CO during pregnancy [3][4][5][6][7][8][11][12][13][14][15][24][25][26][27][28][29][30]32,56,[82][83][84] , and have proved to be reliable when compared with the invasive techniques 3,85,86 . The general availability of ultrasound and its low cost, portability and true non-invasiveness, make TTE an ideal method for rapid hemodynamic assessment in pregnancy.…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%